2014
DOI: 10.1002/ejoc.201402116
|View full text |Cite
|
Sign up to set email alerts
|

α‐Acryloylamidoalkyl Sulfones in a Synthetic Approach for the Preparation of 6‐Alkyltetrahydropyridin‐2‐ones

Abstract: The reaction of allylzinc bromides with α‐acryloylamidoalkyl sulfones represents a mild and straightforward entry to the corresponding homoallylamines. These dienyl compounds successfully proceeded in a ring‐closing metathesis reaction by treatment with Grubbs II catalyst to lead to 6‐alkyltetrahydropyridin‐2‐ones. Homoallylamino derivatives that contain a branched terminal alkene moiety preferentially proceeded in cross‐metathesis reaction to give the selective formation of N‐substituted fumaramides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…It was reasoned that adaptation of the Veenstra protocol would allow us to introduce a second alkene unit during the same process, thus generating a ring-closing metathesis precursor in a single step. This general strategy towards nitrogen heterocycles has been utilized in several reports [20][21][22][23], including asymmetric variants [24,25], but in these cases the ring-closing metathesis precursor was always generated in multiple steps.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reasoned that adaptation of the Veenstra protocol would allow us to introduce a second alkene unit during the same process, thus generating a ring-closing metathesis precursor in a single step. This general strategy towards nitrogen heterocycles has been utilized in several reports [20][21][22][23], including asymmetric variants [24,25], but in these cases the ring-closing metathesis precursor was always generated in multiple steps.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment of diene 5 under ring-closing metathesis conditions, using Grubbs I catalyst, then proceeded to generate the target dihydropyridinone 7 in excellent yield (Scheme 4) [20][21][22][23]26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(7) six-membered ring α,β-unsaturated lactams [652,653], including those employed in syntheses of NSC-134754 (e.g. 249) [654], hippocasine and a diastereomer [655], and sedridine [656]; (8) six-membered ring β,γ-unsaturated lactams [657], including those employed in total syntheses of mehranine and methylenebismehranine and related alkaloids (e.g.…”
Section: )mentioning
confidence: 99%
“…The pKa for the deprotonation of acetylrhenium complex 645 was determined to be 10.6 in acetonitrile. Calorimetric studies of the disproportionation reaction of 649 and 650 to afford the carbonyl (651) and methoxymethyl (652) complexes was determined to be exothermic (∆H = -11.5 kcal/mol). Additional electrochemical studies of metal acyl complexes were also reported.…”
Section: )mentioning
confidence: 99%